A forecasting model to estimate the drop in blood supplies during the SARS‐CoV‐2 pandemic in Italy. Issue 3 (10th March 2021) - Pati, Ilaria; Velati, Claudio; Mengoli, Carlo; Franchini, Massimo; Masiello, Francesca; Marano, Giuseppe; Veropalumbo, Eva; Vaglio, Stefania; Piccinini, Vanessa; Pupella, Simonetta; Liumbruno, Giancarlo M.
Abstract: Objectives: To estimate the number of actually Severe acute respiratory syndrome Coronavirus‐2 (SARS‐CoV‐2) infected blood donors applying a statistical forecasting model. Background: Following the outbreak of the SARS‐CoV‐2 epidemic, a drop in blood donation has been observed. It is crucial to determine the actual number of potential SARS‐CoV‐2‐positive donors to define the measures and ensure adequate blood supply. Methods: The cumulative incidence of SARS‐CoV‐2 positivity, calculated on the general population, was applied to the donor population by estimating the number of positive subjects. The calculation model was validated by the linear interpolation method. The number of blood units actually discarded based on post‐donation information was also taken into account. Results: Three months after the outbreak, 5322 donors were estimated to be positive for SARS‐CoV‐2 and were therefore potentially excluded from donation. A total of units of blood components were discarded following post donation information. The estimated number of donors deceased (180) and the number of clinically recovered individuals in the same period was also considered. Conclusion: This forecasting model can be used to obtain information on blood donors' involvement during future SARS‐CoV‐2 outbreaks, especially in case of changes concerning epidemiology, incidence by age bracket and geographical distribution and also for new outbreaks of emerging viruses.